A Study of Sex Stereotyping in Child-Selected Play Activities of Preschool Children - Beeson, Betty Spillers; Williams, R. Ann ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
The purpose of this study was to examine child-selected play activities of three-, four-, and five-year-old children to determine whether the choices reflected society's traditionally sex stereotyped labels. Subjects were 50 students enrolled in two nursery school programs at a midwestern university during the autumn of 1979. Three observers recorded the number of different boys or girls that participated in the following activities: art projects, house play, wheeled vehicles, sand or water, blocks, climbing apparatus, books, and table activities. The data were collected in 30 minute observation periods over six consecutive weeks. Several findings differ from previous studies. While all four traditionally female-oriented play activities (house play, books, art projects, and table activities) were chosen more by girls than by boys, the difference was not statistically significant at the .05 level. Boys choose the traditionally male-oriented play activities: wheeled vehicles and sand/water, more than girls did. Girls chose the traditionally male-oriented climbing apparatus more frequently than boys did. Differences for these three activities were not significant at the .05 level. Block play was the only activity revealing sex differences at the .05 level. Significantly more boys than girls played with blocks. It is suggested that the changing societal attitude and the national movement toward eliminating sexism is reflected in the play activities of young children. (Author/RH)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Observation; Play; Preschool Children; Sex Differences; Sex Stereotypes; Social Change; Reports, Research; Numerical/Quantitative Data